The effectiveness of Islamic hedging in managing financial risks: An analytical study in light of Sharia objectives and financing structures (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to analyze the concept of hedging financial risks in Islamic financial institutions and to examine the Shariah principles governing hedging practices. The research explores economic, cooperative, and contractual Islamic hedging strategies as viable alternatives to conventional derivatives, which are restricted due to elements of riba, gharar, and speculation. The study adopts descriptive, analytical, and deductive methodologies and relies on contemporary literature and practical experiences of Islamic banks in Malaysia and the GCC.The findings indicate that Islamic banks are more risk-sensitive than conventional banks due to the nature of their contracts, profit-and-loss sharing structures, governance constraints, and liquidity infrastructure. However, Islamic hedging strategies demonstrate strong potential for integrating risk management with real economic activity, achieving a better balance between risk and return. The study also highlights the shortage of specialized expertise in Islamic risk management and the limited development of Shariah-compliant hedging instruments.The study recommends strengthening innovation in Islamic hedging, developing regulatory frameworks, establishing dedicated risk-management units, and drawing on successful international experiences to design hybrid products capable of mitigating financial risks while adhering to Shariah principles.
Keywords: Financial Hedging; Risk Management; Shariah Objectives; Hedging Instruments